Pengaruh Pemberian Pelet dari Lumpur Kolam Ikan dan Kotoran Kambing pada Pertumbuhan dan Produksi Jagung Manis - Putri Tria Santari; Arief Hartono; . Suwarno (Institut Pertanian Bogor, 2019)
A mixture of fishpond sediment and goat manure can be used to increase the growth and yield of sweet corn. This research aimed to determine the effect of pellet from the combination of fishpond sediment and goat manure with a ratio 1:1 on nutrient (N, P, and K) and yield on sweet corn. The land used was Ultisol Dramaga which was located in Cikabayan Experimental Farm, Bogor Agricultural University. The study was conducted in a greenhouse with a Completely Randomized Design (CRD) of one factor with eleven treatments: without treatment (control); standard fertilization (Urea 0.43 ton ha-1, SP-36 0.41 ton ha-1, and KCl 0.25 ton ha-1); three doses of pellet (20 ton ha-1, 30 ton ha-1, and 40 ton ha-1); three doses of fishpond sediments (10 ton ha-1, 15 ton ha-1, and 20 ton ha-1); three doses of goat manure (10 ton ha-1, 15 ton ha-1, and 20 ton ha-1). The result showed that giving 40 ton ha-1 pellet had a significant effect on the increasing pH, ammonium, and the availability of K in Ultisol and nutrient content of P, K, and the weight of dry-grain sweet corn.